Sustentabilidade de unidades de produção agrícola familiar,avaliada pela ferramenta ApoiaNovorural na região do Planalto,Montes Claros MG - Reginaldo Proque (2010)
The goal of this research was to verify the agro-environmental andsocioeconomic sustainability of agro-systems adopted by agricultural families of Planalto community in Montes Claros-MG. The methodology used was the Novo Rural Environmental Impact Evaluation System (APOIA-NovoRural). A quantitative analysis was used. The system was measured in the following dimensions: landscape ecology; quality of environmental compartment atmosphere, water, soil; socio-cultural values; economical values; management and administration, involving 62 indicators. As the indicators results linked to the ecology of landscape; the environmental quality of the atmosphere, water and soil; Economical Values, all of the unities showed values above the reference value (baseline 0,70), being 0,71; 0,73 and 0,72 to the landscape ecology, respectively, to the unities 1,2 and 3, that shows a existing harmony between the agricultural activities and environmental conservation. As for the environmental quality of the atmosphere, water and soil were average of 0,78; 0,81 and 0,8, respectively, to the unities 1,2 e 3. That data showed that the agricultural activity has not polluted the water resources nor harmed the air quality and the soil contains chemical properties that guarantee the good development of the plants. To economical values, thefound values were 0,83. 0,81 and 0,8, respectively, to the unities 1, 2 and 3, which shows that the remuneration fo the farmers is satisfactory. To the indicators linked to socio-cultural and management/administration values, all of the unities showed values below the reference value (baseline 0,70), being 0,60, 0,61 and 0,62, respectively, to the unities 1, 2 and 3, to the indicators of socio-cultural dimension values. The poor access to employment and the exposition to pesticides contributed significantly to the low value showed in the unities 1, 2 e 3. To the management and administration indicators, all of the productive had a performance below the reference value (baseline 0,7), being 0,42, 0,49 and 0,51, respectively, to the unities 1, 2 and 3. The non existence of basic practices of the cash flow and the precarious managementof residues contributed significantly to the unsatisfying of the productiveunities. The final values presented by the unities 1, 2 and 3 were above the reference value (Baseline 0,70), respectively (0,70, 0,72 and 0,72). We conclude that all of the researched productive unities got a good performance and that they are sustainable regarding the adopted methodology. However, as this methodology does not use the agro-ecological transition principles, it has to be used only as a complimentary method.